C-Geranylated flavonoids from Paulownia tomentosa fruits with antimicrobial potential and synergistic activity with antibiotics. (2nd August 2016) - Navrátilová, Alice; Nešuta, Ondřej; Vančatová, Irena; Čížek, Alois; Varela-M, Ruben E.; López-Abán, Julio; Villa-Pulgarin, Janny A.; Mollinedo, Faustino; Muro, Antonio; Žemličková, Helena; Kadlecová, Daniela; Šmejkal, Karel
Abstract: Context C-6-Geranylated flavonoids possess promising biological activities. These substances could be a source of lead compounds for the development of therapeutics. Objective The study was designed to evaluate their antibacterial and antileishmanial activity. Materials and methods C-6-Geranylated flavanones were tested in micromolar concentrations against promastigote forms of Leishmania brazilensis, L. donovani, L. infantum, and L. panamensis against methicillin-resistant Staphylococcus aureus (MRSA); and synergistic potential with antibiotics was analyzed. IC50 values (after 72 h) were calculated and compared with that of miltefosine. Flow cytometry and DNA fragmentation analysis were used the mechanism of the effect. Geranylated flavanones or epigallocatechin gallate were combined with oxacillin, tetracycline, and ciprofloxacin, and the effects of these two-component combinations were evaluated. Minimal inhibitory concentrations (MICs) and minimal bactericidal concentrations (MBCs) were established (after 24 h), the synergy was measured by the checkerboard titration technique, and the sums of the fractional inhibitory concentrations (∑FICs) were computed. Results 3′- O -Methyl-5′- O -methyldiplacone and 3′- O -methyldiplacone showed good antileishmanial activities (IC50 8–42 μM). 3′- O -Methyl-5′-hydroxydiplacone activates the apoptotic death at leishmanias, the effect of 3′- O -methyl-5′- O -methyldiplacone has another mechanism. The test of the antibacterial activity showed good effects of 3′- O -methyldiplacol and mimulone against MRSA (MIC 2–16 μg/mL), and in six cases, the results showed synergistic effects when combined with oxacillin. Synergistic effects were also found for the combination of epigallocatechin gallate with tetracycline or oxacillin. Conclusion This work demonstrates anti-MRSA and antileishmanial potential of geranylated flavanones and uncovers their promising synergistic activities with antibiotics. In addition, the mechanism of antileishmanial effect is proposed.